2018
DOI: 10.1002/pip.3067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat‐bias soaking on cesium fluoride‐treated CIGS thin film solar cells

Abstract: The combined effect of heating and forward bias voltage, that is, heat‐bias soaking (HBS) on cesium fluoride (CsF)‐free and CsF‐treated Cu(In1‐xGax)Se2 (CIGS) solar cells using chemical bath deposition‐cadmium sulfide (CBD‐CdS) buffer layer was investigated with varying the heating temperature, bias voltage, and biasing time. Heat bias soaking followed by heat soaking (HS) (ie, HBS/HS) treatments improved the open‐circuit voltage (VOC) and conversion efficiency for the CsF‐treated CIGS solar cell, whereas such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 34 publications
4
32
1
Order By: Relevance
“…The performance was even higher than that initially with efficiency rising from 16.0% to 16.6%, after HLS, owing to the improvement in open‐circuit voltage. This result is consistent with previous reports of HLS or heat‐bias soaking (HBS) on alkali‐treated CIGS solar cells, where an electric field generated in the CIGS absorber by light irradiation (or forward bias) was suggested as a driving force for the effect.…”
Section: J–v Parameters Of Csf‐free and Csf‐treated Cigs Solar Cells supporting
confidence: 93%
See 1 more Smart Citation
“…The performance was even higher than that initially with efficiency rising from 16.0% to 16.6%, after HLS, owing to the improvement in open‐circuit voltage. This result is consistent with previous reports of HLS or heat‐bias soaking (HBS) on alkali‐treated CIGS solar cells, where an electric field generated in the CIGS absorber by light irradiation (or forward bias) was suggested as a driving force for the effect.…”
Section: J–v Parameters Of Csf‐free and Csf‐treated Cigs Solar Cells supporting
confidence: 93%
“…The completed solar cell structure was Al/Ni/ZnO:Al (300 nm)/ZnO (100 nm)/CdS (60 nm)/CIGS (2.5–3.0 μm)/Mo (600 nm)/SLG. CsF‐treated CIGS solar cells were prepared as mentioned in the previous report …”
Section: Methodsmentioning
confidence: 99%
“…Alkali‐elements in CIGSe films are also likely correlated with metastable properties, for example, light‐soaking or bias‐induced effects . CGSe cells showed no significant improvements in V oc and FF but showed an enhancement in J sc values as mentioned above (Figure ).…”
Section: Cgse Thin Films and Solar Cellsmentioning
confidence: 71%
“…A buried p‐n junction model has been suggested as the operating principle of CIGSe cells . Group II elements such as Cd or Zn are believed to diffuse into the CIGSe film surface during the deposition process of an n ‐type buffer‐layer such as CdS or ZnS(O,OH) on a CIGSe film.…”
Section: Cgse Thin Films and Solar Cellsmentioning
confidence: 99%
“…This indicates that CsF‐treated CIGS solar cells are applicable to terrestrial and space applications. Furthermore, our previous studies revealed the beneficial effect of heat‐light soaking (HLS) or heat‐bias soaking (HBS) on alkali metal‐treated CIGS solar cells. These post‐treatments increased the efficiency ( η ) of solar cells by enhancing the open‐circuit voltage ( V OC ).…”
mentioning
confidence: 99%